Tributyltin exposure increases mortality of nodavirus infected Japanese medaka Oryzias latipes larvae. Issue 2 (30th November 2017) - Kitamura, Shin-Ichi; Akizuki, Masaki; Song, Jun-Young; Nakayama, Kei
Abstract: We investigated the effect of combined exposure to nodavirus infection and TBT on medaka ( Oryzias latipes ). Medaka larvae were infected by immersion in medium containing nodavirus at titers of 10 2.5, 10 3.5, or 10 4.5 TCID50 /mL. Infected fish then were exposed to TBT at 0, 0.17, 0.52, 1.6, or 4.7 μg/L. Of the 12 groups exposed to both stressors, the mortalities of 6 (10 2.5 TCID50 /mL + 0.52, 1.6, or 4.7 μg/L, 10 3.5 TCID50 /mL + 4.7 μg/L and 10 4.5 TCID50 /mL + 1.6 or 4.7 μg/L) were significantly higher than that of each TBT control. Specifically, mortality was 46 ± 5.5% in the group exposed to both 10 2.5 TCID50 /mL virus and 0.52 μg/L TBT, which represent the lowest observed effective dose and concentration, respectively, among the 6 groups with increased mortalities. Our results suggest that combined exposure to both stressors suppresses antiviral mechanisms in the fish, thus increasing mortality. Highlights: The effect of combined nodavirus infection and TBT exposure was assessed in medaka. Mortality was higher in fish exposed to both stressors compared with a single one. Viral LOED was 10 2.5 TCID50 /mL and TBT LOEC was 0.52 μg/L as combined stressors.